2014
DOI: 10.1038/nm.3617
|View full text |Cite
|
Sign up to set email alerts
|

Huntington's disease is a four-repeat tauopathy with tau nuclear rods

Abstract: An imbalance of tau isoforms containing either three or four microtubule-binding repeats causes frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP-17) in families with intronic mutations in the MAPT gene. Here we report equivalent imbalances at the mRNA and protein levels and increased total tau levels in the brains of subjects with Huntington's disease (HD) together with rod-like tau deposits along neuronal nuclei. These tau nuclear rods show an ordered filamentous ultrastructure and can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
204
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(237 citation statements)
references
References 27 publications
21
204
4
Order By: Relevance
“…Through such convergent screens, we found that TRIM28 regulates the levels of both disease-driving proteins. Our finding that TRIM28 regulates α-Syn and tau by promoting their nuclear localization and accumulation dovetails nicely with studies indicating that altered cellular distribution of α-Syn and tau contributes to neurodegeneration (Fares et al, 2014; Fernández-Nogales et al, 2014; Kontopoulos et al, 2006). Indeed, several lines of evidence suggest that mislocalization or missorting of α-Syn and tau as a result of mutations, post-translational modification or overexpression, rather than their respective aggregation in the form of Lewy bodies and NFTs, are what promotes neurodegeneration (Frandemiche et al, 2014; Wilson et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…Through such convergent screens, we found that TRIM28 regulates the levels of both disease-driving proteins. Our finding that TRIM28 regulates α-Syn and tau by promoting their nuclear localization and accumulation dovetails nicely with studies indicating that altered cellular distribution of α-Syn and tau contributes to neurodegeneration (Fares et al, 2014; Fernández-Nogales et al, 2014; Kontopoulos et al, 2006). Indeed, several lines of evidence suggest that mislocalization or missorting of α-Syn and tau as a result of mutations, post-translational modification or overexpression, rather than their respective aggregation in the form of Lewy bodies and NFTs, are what promotes neurodegeneration (Frandemiche et al, 2014; Wilson et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…It might be expected that such an RNA toxicity based mechanism would have additional wide-spread consequences on global alternative splicing, similar to sequestration of MBNL1 in myotonic dystrophy. In fact, an unpublished study has identified various alternatively spliced transcripts in HD mouse model tissue (Gipson TA and Housman DE, unpublished data) and an increase of the 4R/3R tau mRNA ratio has been observed [59]. Intriguingly, we identified at least one module that was significantly enriched for genes involved in RNA binding/mRNA processing in all three brain region networks (Tables 1, 2 and 3), which had not been discovered in the original publication.…”
Section: Discussionmentioning
confidence: 99%
“…Tau repeat domains bind at the interface between α- and β-tubulin heterodimers, suggesting that there is competition between their physiological interaction with tubulin and pathogenic misfolding (Kadavath et al, 2015). Most recently, Huntington’s disease has been confirmed as 4R tauopathy (Fernández-Nogales et al, 2014). …”
Section: Clinical and Neuropathological Criteria For Ad Diagnosismentioning
confidence: 99%